A framework for the continuous monitoring of person-centred hospital care: validation of a checklist for participatory service improvement - F. Cardinali; S. Carzaniga; L. Martini; M. T. Loiudice; Fabrizio Carinci (Archives of Public Health)
Abstract Background In 2018, a nationwide survey carried out in 387 acute care hospitals from 16 out of 21 Italian regions, allowed defining an extended checklist for the participatory evaluation of person-centredness in hospital care. We aimed to validate a reduced set of core items for continuous use across the country. Methods Factor analysis was used to validate the construct of the checklist. Varimax rotation with eigenvalues > 1 was used to optimize factor structure. Items with an item-total correlation > 0.30 and factor loadings > 0.4 were attributed to individual factors. Items with inter-item correlation coefficient > 0.70 were submitted to expert opinion for final decision. Overall internal consistency was assessed through Cronbach’s alpha. Results A total of 183 out of 243 items in the original checklist were submitted to factor analysis. A subgroup of 67 items was retained in 4 main areas, allocated as follows: 16 items in 4 sub-areas of “Person-oriented organizational and care processes”, 16 items in 4 sub-areas of “Physical accessibility, liveability and comfort of the facilities”, 15 items in 3 sub-areas of “Access to information, streamlining and transparency”, and 20 items in 4 sub-areas of “Taking care of the relationship with patients and citizens”. Overall values of Cronbach’s alpha ranged between 0.77 and 0.90, showing high consistency. Conclusions This study validated a “core” checklist that can be routinely used to monitor the implementation of person-centred care in Italian hospitals. The tool can be applied more widely by multiple stakeholders as a measurement instrument for the participatory evaluation of person-centredness.